57.5k views
1 vote
The equation 2x2 − 3x + 1 = 0 is in quadratic form. true or false

User Bbuecherl
by
5.0k points

2 Answers

6 votes

Answer:

True.

Explanation:

The equation
2x^(2) - 3x + 1 = 0 is in quadratic form because it meets the quadratic formula:
Ax^(2) + Bx + C = 0.

User Jan Hettich
by
5.1k points
12 votes

Answer:

True

Explanation:

The equation 2x² - 3x + 1 = 0 is in quadratic form.

User KANAYO AUGUSTIN UG
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.